Diallyl sulfide from garlic suppresses quorum‐sensing systems of Pseudomonas aeruginosa and enhances biosynthesis of three B vitamins through its thioether group. Issue 2 (30th December 2020) - Li, Wen‐Ru; Zeng, Tao‐Hua; Yao, Jun‐Wei; Zhu, Li‐Ping; Zhang, Zhi‐Qing; Xie, Xiao‐Bao; Shi, Qing‐Shan
Summary: Diallyl sulfide (DAS) and diallyl disulfide (DADS), two constituents of garlic, can inhibit quorum sensing (QS) systems of Pseudomonas aeruginosa . However, the differences in the mechanism of QS inhibition between DAS and DADS, and the functional chemical groups of these sulfides that contribute in QS inhibition have not been elucidated yet. We assumed that the sulfide group might play a key role in QS inhibition. To prove this hypothesis and to clarify these unsolved problems, in this study, we synthesized diallyl ether (DAE), and compared and investigated the effects of DAS and DAE on the growth and production of virulence factors, including Pseudomonas quinolone signal (PQS), elastase and pyocyanin, of P. aeruginosa PAO1. Transcriptome analysis and qRT‐PCR were used to compare and analyse the differentially expressed genes between the different treatment groups (DAS, DAE and control). The results indicated that DAS did not affect the growth dynamics of P. aeruginosa PAO1; however, DAS inhibited transcription of most of the QS system genes, including lasR, rhlI / rhlR and pqsABCDE / pqsR ; thus, biosynthesis of the signal molecules C4 ‐HSL (encoded by rhl I) and PQS (encoded by pqsABCDE ) was inhibited. Furthermore, DAS inhibited the transcription of virulence genes regulated by the QS systems, including rhlABC, lasA, lasB, lecA and phzAB, phzDEFG, phzM and phzS that encode for rhamnolipid, exoprotease, elastase, lectin and pyocyanin biosynthesis respectively. DAS also enhanced the expression of the key genes involved in the biosynthesis of three B vitamins: folate, thiamine and riboflavin. In conclusion, DAS suppressed the production of some virulence factors toxic to the host and enhanced the production of some nutrition factors beneficial to the host. These actions of DAS may be due to its thioether group. These findings would be significant for development of an effective drug to control the virulence and pathogenesis of the opportunistic pathogen P. aeruginosa . Abstract : Diallyl disulfide (DAS) from garlic did not affect the growth dynamics of Pseudomonas aeruginosa PAO1; however, DAS inhibited transcription of most of the quorum sensing (QS) system genes, including lasR, rhlI/rhlR, and pqsABCDE/pqsR; thus, biosynthesis of the signal molecules C4‐HSL (encoded by rhlI) and PQS (encoded by pqsABCDE) was inhibited.DAS suppressed the production of some virulence factors toxic to the host and enhanced the production of some nutrition factors beneficial to the host. These actions of DAS may be due to its thioether group.